Neurodevelopmental outcomes at 7 years' corrected age in preterm infants who were fed high-dose docosahexaenoic acid to term equivalent: a follow-up of a randomised controlled trial. Issue 3 (18th March 2015) - Collins, Carmel T; Gibson, Robert A; Anderson, Peter J; McPhee, Andrew J; Sullivan, Thomas R; Gould, Jacqueline F; Ryan, Philip; Doyle, Lex W; Davis, Peter G; McMichael, Judy E; French, Noel P; Colditz, Paul B; et al.
Abstract : Objective: To determine if improvements in cognitive outcome detected at 18 months' corrected age (CA) in infants born <33 weeks' gestation receiving a high-docosahexaenoic acid (DHA) compared with standard-DHA diet were sustained in early childhood. Design: Follow-up of a multicentre randomised controlled trial. Randomisation was stratified for sex, birth weight (<1250 vs ≥1250 g) and hospital. Setting: Five Australian tertiary hospitals from 2008 to 2013. Participants: 626 of the 657 participants randomised between 2001 and 2005 were eligible to participate. Interventions: High-DHA (≈1% total fatty acids) enteral feeds compared with standard-DHA (≈0.3% total fatty acids) from age 2–4 days until term CA. Primary outcome: Full Scale IQ of the Wechsler Abbreviated Scale of Intelligence (WASI) at 7 years CA. Prespecified subgroup analyses based on the randomisation strata (sex, birth weight) were conducted. Results: 604 (92% of the 657 originally randomised) consented to participate (291 high-DHA, 313 standard-DHA). To address missing data in the 604 consenting participants (22 for primary outcome), multiple imputation was performed. The Full Scale IQ was not significantly different between groups (high-DHA 98.3, SD 14.0, standard-DHA 98.5, SD 14.9; mean difference adjusted for sex, birthweight strata and hospital −0.3, 95% CI −2.9 to 2.2; p=0.79). There were no significant differences in any secondary outcomes. In prespecified subgroup analyses, there was a significant sex by treatment interaction on measures of parent-reported executive function and behaviour. Scores were within the normal range but girls receiving the high-DHA diet scored significantly higher (poorer outcome) compared with girls receiving the standard-DHA diet. Conclusions: Supplementing the diets of preterm infants with a DHA dose of approximately 1% total fatty acids from days 2–4 until term CA showed no evidence of benefit at 7 years' CA. Trial registration number: Australian New Zealand Clinical Trials Registry: ACTRN12606000327583.